2014
DOI: 10.1016/j.crm.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-meteorology and scientific weather forecasting: Small farmers and scientists’ perspectives on climate variability in the Okavango Delta, Botswana

Abstract: a b s t r a c tRecent trends in abrupt weather changes continue to pose a challenge to agricultural production most especially in sub-Saharan Africa. The paper specifically addresses the questions on how local farmers read and predict the weather; and how they can collaborate with weather scientists in devising adaptation strategies for climate variability (CV) in the Okavango Delta of Botswana. Recent trends in agriculture-related weather variables available from country's climate services, as well as in free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 16 publications
3
67
0
1
Order By: Relevance
“…Forecasts accuracy tends to decrease with smaller regions and locally specific information tends to be more uncertain and making this information more accurate requires sufficient observational records in order to be meaningful (Goddard et al, 2010;Gong et al, 2003). Inaccurate forecasts have been implicated in negative yield impacts and the opportunity costs for uncertain forecast is substantial and compromises profitability (Kolawole et al, 2014;Roudier et al, 2014). Farmers in Zimbabwe, and in eastern Africa, have demonstrated that, with some help, they are able to understand and incorporate probabilistic forecast information into their decision making processes Luseno et al, 2003;Lybbert et al, 2007;Patt, 2001;Suarez & Patt, 2004).…”
Section: Sources Of Seasonal Climate Forecast Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Forecasts accuracy tends to decrease with smaller regions and locally specific information tends to be more uncertain and making this information more accurate requires sufficient observational records in order to be meaningful (Goddard et al, 2010;Gong et al, 2003). Inaccurate forecasts have been implicated in negative yield impacts and the opportunity costs for uncertain forecast is substantial and compromises profitability (Kolawole et al, 2014;Roudier et al, 2014). Farmers in Zimbabwe, and in eastern Africa, have demonstrated that, with some help, they are able to understand and incorporate probabilistic forecast information into their decision making processes Luseno et al, 2003;Lybbert et al, 2007;Patt, 2001;Suarez & Patt, 2004).…”
Section: Sources Of Seasonal Climate Forecast Informationmentioning
confidence: 99%
“…There is need to generate useful climate information and predictions and translate that information into usable forms for decision makers through continued dialogues among users of the information periodically. Information tends to be applicable to relatively large areas and lacks specificity, including the fact that information is disseminated late and in unfriendly languages, with technical jargon that makes it limit the effectiveness of uptake (Goddard et al, 2010;Hansen et al, 2009;Kolawole et al, 2014;Van Aalst et al, 2008cited in Mapfumo et al, 2015Mberego & Sanga-Ngoie, 2012;Patt & Gwata, 2002). There is also lack of specific information about timing of rainfall and season onset or length, including the late dissemination of the information (Hansen et al, 2011;Kolawole et al, 2014).…”
Section: Sources Of Seasonal Climate Forecast Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the tensions evident in Monze, future research could explore the complementarity of knowledge forms in forecasting rainfall (e.g. Kolawole et al 2014), thus creating a space for bridging epistemologies. Wisner (2010a) highlights the potential (and pitfalls) of participatory action research methods in successfully bridging and co-producing hybrid knowledge.…”
Section: Discussionmentioning
confidence: 99%